IMPROVED KNOWLEDGE AND REPORTING OF PATIENT SAFETY INCIDENTS BY NURSE EXECUTIVES AFTER ACADEMIC MODEL SUPERVISION IN X HOSPITAL, CIREBON CITY - Anita Anita (Jurnal Ilmiah Perawat Manado (Juiperdo), 2021)
ABSTRAK Insiden keselamatan pasien (IKP) di RS X yang tidak dilaporkan dalam sistem Q pulse 36%. Pelaporan IKP merupakan salah satu kendali mutu agar kejadian yang sama tidak terulang kembali. Tidak terlapornya IKP dipengaruhi oleh faktor supervisi, usia, jenis kelamin, tingkat pendidikan, lama kerja dan supervisi model akademik. Penelitian dilakukan di RS X menilai peningkatan pengetahuan dan pelaporan IKP oleh perawat pelaksana setelah supervisi model akademik dengan kegiatan educative, supportive, dan managerial. Penelitian menggunakan one group pre-test and posttest design dilakukan bulan Mei -Juli 2021. Alat ukur menggunakan kuesioner valid dan reliabel kepada 77 responden perawat pelaksana dan dianalisis menggunakan uji Wilcoxon dan uji Chi Square. Hasil penelitian menunjukkan pengetahuan IKP rerata nilai 76.88 dan jumlah pelaporan IKP 54,5%. Peningkatan pengetahuan IKP perawat pelaksana setelah supervisi model akademik 3,38 (0,043%). Angka pelaporan IKP sesudah supervisi model akademik meningkat (43,9%). Tidak ada hubungan antara karakteristik perawat dan peningkatan pengetahuan IKP perawat pelaksana setelah supervisi model akademik dengan p value >0.05. Tidak ada hubungan antara karakteristik dan peningkatan pelaporan IKP oleh perawat pelaksana setelah supervisi model akademik. Penelitian merekomendasikan pemberian resosialisasi supervisi model akademik agar konsisten, pendampingan dan penguatan motivasi dari pimpinan dan peer group untuk saling menguatkan. Perlu penelitian mendalam melalui mixed metode kepatuhan pelaporan IKP. Kata Kunci: Insiden Keselamatan Pasien; Pengetahuan; Pelaporan; Perawat pelaksana; Supervisi model akademik. ABSTRACT Patient safety incidents (PSI) in Hospital X that were not reported in the Q pulse system were 36%. IKP reporting is one of the quality controls so that the same incident does not happen again. Unreported PSI is influenced by factors of supervision, age, gender, education level, length of work and supervision of the academic model. The study was conducted at the Hospital X assessing the increase in knowledge and reporting of PSI by implementing nurses after supervision of the academic model with educative, supportive, and managerial activities. The study used a one group pre-test and posttest design carried out in May-July 2021. The measuring instrument used a valid and reliable questionnaire to 77 implementing nurse respondents and analyzed using the Wilcoxon test and Chi Square test. The results showed that the average PSI knowledge was 76.88 and the number of reporting PSI was 54.5%. The increase in PSI knowledge of implementing nurses after supervision of the academic model was 3.38 (0.043%). The PSI reporting rate after supervision of the academic model increased (43.9%). There is no relationship between the characteristics of nurses and the increase in PSI knowledge of implementing nurses after supervision of the academic model with p value > 0.05. There is no relationship between the characteristics and the increase in PSI reporting by nurses after supervision of the academic model. The research recommends providing resocialization of academic model supervision so that it is consistent, mentoring and strengthening motivation from leaders and peer groups to strengthen each other. In-depth research is needed through mixed methods of PSI reporting compliance. Keywords: Patient Safety Incident; Knowledge; Reporting; Nurse implementing; Supervision of academic model.